TOLL-LIKE RECEPTORS (TLR) 2 AND 4 EXPRESSION OF KERATINOCYTES FROM PATIENTS WITH LOCALIZED AND DISSEMINATED DERMATOPHYTOSIS - de Oliveira, Cristiane Beatriz (Rev Inst Med Trop Sao Paulo, 2015)
There are few studies on the role of innate immune response in dermatophytosis. An investigation was conducted to define the involvement of Toll-Like Receptors (TLRs) 2 and 4 in localized (LD) and disseminated (DD) dermatophytosis due to T. rubrum. Fifteen newly diagnosed patients, eight patients with LD and seven with DD, defined by involvement of at least three body segments were used in this study. Controls comprised twenty skin samples from healthy individuals undergoing plastic surgery. TLR2 and TLR4 were quantified in skin lesions by immunohistochemistry. A reduced expression of TLR4 in the lower and upper epidermis of both LD and DD patients was found compared to controls; TLR2 expression was preserved in the upper and lower epidermis of all three groups. As TLR4 signaling induces the production of inflammatory cytokines and neutrophils recruitment, its reduced expression likely contributed to the lack of resolution of the infection and the consequent chronic nature of the dermatophytosis. As TLR2 expression acts to limit the inflammatory process and preserves the epidermal structure, its preserved expression may also contribute to the persistent infection and limited inflammation that are characteristic of dermatophytic infections.